The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1017/cbo9781107337480
|View full text |Cite
|
Sign up to set email alerts
|

Archaic Style in English Literature, 1590–1674

Abstract: Ranging from the works of Shakespeare, Spenser, Jonson and Milton to those of Robert Southwell and Anna Trapnel, this groundbreaking study explores the conscious use of archaic style by the poets and dramatists between 1590 and 1674. It focuses on the wide-ranging, complex and self-conscious uses of archaic linguistic and poetic style, analysing the uses to which writers put literary style in order to re-embody and reshape the past. Munro brings together scholarly conversations on temporality, memory and histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…It is as part of this sequence that Robert Greene's Greene's Vision (1592) needs to be read. Scholars such as Cooper (2005) and Munro (2013) have been interested in the medievalism of Greene's text, especially its staged debate between the figures of Chaucer and Gower; and Maslen (2008) relates it to a wider group of "repentance" narratives attached to Greene. However, Greene's "vision" of the great Ricardian poets is part of the very peculiar mechanics of the text as a whole, and of how his text functioned within the sequence of medievalist texts of which it is an immediate part.…”
Section: Temporality and Extemporality: The Medievalist Moment Of Elizabethan Prose Fictionmentioning
confidence: 99%
“…It is as part of this sequence that Robert Greene's Greene's Vision (1592) needs to be read. Scholars such as Cooper (2005) and Munro (2013) have been interested in the medievalism of Greene's text, especially its staged debate between the figures of Chaucer and Gower; and Maslen (2008) relates it to a wider group of "repentance" narratives attached to Greene. However, Greene's "vision" of the great Ricardian poets is part of the very peculiar mechanics of the text as a whole, and of how his text functioned within the sequence of medievalist texts of which it is an immediate part.…”
Section: Temporality and Extemporality: The Medievalist Moment Of Elizabethan Prose Fictionmentioning
confidence: 99%
“…Writers frequently echo or imitate their artistic forebears, but the process of reworking outmoded styles tends to result in new hybrid forms. 23 Fredson Bowers offers a useful (if hostile) survey of how revenge tragedy was refashioned in the Caroline era, with Fletcherian mannerisms to the fore. 24 He detects no such influence on Alphonsus, though, seeing the play as very much of the Elizabethan moment, written under the sway of Kyd and Marlowe.…”
mentioning
confidence: 99%
“…These imitations do not solely invoke Herbert as a model of how to combine devotional poetry with moral wisdom, however. Munro's work on conscious archaism in early‐modern literature has indicated that a text can ‘survive the moment of its original production’, and may then be deliberately re‐used as a ‘calculated continuity, or re‐evocation’ at a subsequent point in time (Munro, , p. 4). By drawing on the wisdom of Herbert's poem, penned at least twenty years prior to both the mid‐century's turmoil and the time in which Baxter, Bryan, and Wanley were writing, their use of The Temple allows their texts to look both backwards and forwards.…”
mentioning
confidence: 99%